WORLD CLASS UNIVERSITY: DEFINITION AND POLICY MODEL IN INDONESIAN HIGHER EDUCATION - Ayu Anastasya Rachman (Journal of Governance and Global Studies, 2024)
Nowadays, building the World Class University (WCU) is one of the ways to improve the nation’s competitiveness in the global knowledge economy. Many countries try to come up with the policy reform’s strategy to accomplish the mission. This is challenging for Indonesia as it is the fourth- largest education system in the world. We conduct qualitative research through the assessment of literature. We argue that there are many ways to interpret the methodology of WCU to which depends on individual ranking promoters. With the lack of equity in the policy model, Indonesia HEIs face double burden to pursue world university ranking and satisfied the clustering system at home. In this article we try to find a consensus about WCU in Indonesian Higher Education.